Pregnancy Outcome after Varenicline Exposure in the First Trimester - Yusuf Cem Kaplan; Nihal Olgac Dündar; Burcu Kasap; Barıs Karadas (Case Reports in Obstetrics and Gynecology)
To the best of our knowledge this is the first case report describing exposure to varenicline, an α4β2 nicotinic acetylcholine partial receptor agonist used for smoking cessation therapy in pregnancy. A 29-year-old multiparous woman with an unplanned pregnancy has used varenicline 2 mg/day unintentionally yet regularly 4 weeks from her last menstrual period. Fetal ultrasound performed at each trimester, detailed anomaly scan, and fetal echocardiography which were performed at the 22nd gestational week showed normal fetal growth with no malformations. The patient delivered a healthy baby at the 38th week of gestation with normal Apgar score and physical examination findings. Age-appropriate physical and neurological development of the child has been observed for 6 months. Although it is not possible to draw definitive conclusions, this case report may contribute to the current available limited data regarding the safety of varenicline use in pregnancy.